2022
DOI: 10.1155/2022/9716224
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effect of Bisphenol A‐Mediated RBP‐4 on Pregnancy Outcomes in Nonobese Pregnant Female with Subclinical Hypothyroidism

Abstract: Hypothyroidism is a systemic hypometabolic syndrome caused by the thyroxine resistance or a reduction in its extent. It is an endocrinopathy secondary to gestational diabetes and occurs usually without significant symptoms. This study explored the effect of bisphenol A (BPA)-mediated retinol-binding protein 4 (RBP-4) on pregnancy outcomes in a nonobese pregnant female with subclinical hypothyroidism. Three hundred nonobese pregnant females who had that established pregnancy files and had regular obstetric exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…4 Moreover, the risk of maternal and neonatal adverse outcomes also depends on various factors, such as lipid differences 5 and pregnancy complications. 6 An increasing number of research works [7][8][9] are finding many risk factors associated with adverse maternal and neonatal outcomes, such as lipid levels, bisphenol A, retinol-binding protein 4, and first trimester thyroid stimulating hormone. However, these studies have mostly focused on individual components, and there is currently no comprehensive model available to predict the overall risk of maternal and neonatal adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, the risk of maternal and neonatal adverse outcomes also depends on various factors, such as lipid differences 5 and pregnancy complications. 6 An increasing number of research works [7][8][9] are finding many risk factors associated with adverse maternal and neonatal outcomes, such as lipid levels, bisphenol A, retinol-binding protein 4, and first trimester thyroid stimulating hormone. However, these studies have mostly focused on individual components, and there is currently no comprehensive model available to predict the overall risk of maternal and neonatal adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more studies [9][10][11] have identi ed some risk factors leading to adverse maternal and infant outcomes, but most of them are single factors, and there is no relevant model to comprehensively predict the risk of adverse maternal and infant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%